Management takeover battles and the role of the golden handshake - Oliver Fabel; Martin Kolmar (Universität Konstanz, Fachbereich Wirtschaftswissenschaften, 2002)
The effect of severance pay on management behavior during a takeover battle is generally ambiguous. Yet, the severance payment completely restraining all influence activities always constitutes a golden handshake. The manager leaving office still benefits from the increase in the merged firm's total value. Moreover, given that the managers are compensated according to an identical linear incentive scheme, the optimal shareholder policy always entails a corner solution. Managers will either receive no severance pay, or the payment will be chosen such that their influence activities equal zero. Relatively strong incentive intensities and low synergy gains then imply that offering no severance pay dominates.
Keywords: G34; M12; 330; mergers; contests; golden handshakes